2022
DOI: 10.1002/brb3.2697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive transcranial magnetic stimulation on gait disorders and cognitive dysfunction in Parkinson's disease: A systematic review with meta‐analysis

Abstract: Background Repetitive transcranial magnetic stimulation (rTMS) is acknowledged to be crucial to manage freezing of gait (FOG) and cognitive impairment for patients with Parkinson's disease (PD), but its effectiveness is unclear. Objective To determine the effects of rTMS on FOG and cognitive function in people with PD and to investigate potential factors that modulate the rTMS effects. Methods Databases searched included PubMed, Web of Science, EMBASE, and the Cochrane Library from inception to December 31, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…According to our analysis, two factors may have caused the above results. First, we consider that the diversity of the stimulation protocols utilized in each study was the cause (Lee et al, 2019;Nardone et al, 2020;de Oliveira et al, 2021;Nascimento et al, 2021;Pol et al, 2021;Deng et al, 2022;Krogh et al, 2022). Although our results did not reveal a statistically significant relationship between NIBS and gait speed, balance, or stride length, this does not mean that NIBS does not affect these outcomes.…”
Section: Figurementioning
confidence: 55%
See 3 more Smart Citations
“…According to our analysis, two factors may have caused the above results. First, we consider that the diversity of the stimulation protocols utilized in each study was the cause (Lee et al, 2019;Nardone et al, 2020;de Oliveira et al, 2021;Nascimento et al, 2021;Pol et al, 2021;Deng et al, 2022;Krogh et al, 2022). Although our results did not reveal a statistically significant relationship between NIBS and gait speed, balance, or stride length, this does not mean that NIBS does not affect these outcomes.…”
Section: Figurementioning
confidence: 55%
“…There have been previous studies on the impact of NIBS on PD ( Helmich et al, 2006 ; Benninger and Hallett, 2015 ; Elsner et al, 2016 ), as well as several systematic reviews and meta-analyses ( Chou et al, 2015 ; Kim et al, 2019 ; Lee et al, 2019 ; Nardone et al, 2020 ; de Oliveira et al, 2021 ; Nascimento et al, 2021 ; Pol et al, 2021 ; Deng et al, 2022 ; Krogh et al, 2022 ). These studies assessed the effect of NIBS on motor symptoms ( de Oliveira et al, 2021 ), dyskinesia ( de Oliveira et al, 2021 ), and gait function ( Nardone et al, 2020 ; Pol et al, 2021 ; Deng et al, 2022 ) associated with PD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in the follow-up, the total number of unbalanced TCMC types owned by one person has increased, indicating an individual's health status could develop TCMC types. It is confirmed that TCMC types can influence the development of the disease [23,24]. Earlier, a pilot study recruited 218 participants with hepatic disease resulting in phlegm and dampness in the meridian during the early stage.…”
Section: Influencing Factors Related To Unbalanced Tcmc Types and The...mentioning
confidence: 84%